2010
DOI: 10.1016/j.schres.2010.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Striatal volumes and dyskinetic movements in youth at high-risk for psychosis

Abstract: Although dyskinesias may be one of the first behavioral indicators of progressive striatal dysfunction, a mechanism critically implicated in the pathogenesis of psychotic disorders, little is known about the association between striatal structures and abnormal movements in high-risk populations. Thirty participants with a prodromal syndrome were rated for dyskinetic movements and underwent structural magnetic resonance imaging (MRI). Volumes of striatal brain structures were delineated. Elevated hyperkinetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 11 publications
2
52
1
Order By: Relevance
“…Indeed, relevant research in UHR and first episode psychosis patients also shows that motor function associated with neurologic soft sign exams and spontaneous Parkinsonisms predict cognitive impairment and worsening negative symptoms (Cuesta et al, 2014; Dean and Mittal, 2014; Mittal et al, 2014). In contrast to the current results, hyperkinetic movements (e.g., dyskinesias) appear to be more closely linked to aberrant dopaminergic processes and predict exacerbation of positive symptoms (Callaway et al, 2014; Mittal et al, 2010; Mittal et al, 2008; Mittal et al, 2007). …”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, relevant research in UHR and first episode psychosis patients also shows that motor function associated with neurologic soft sign exams and spontaneous Parkinsonisms predict cognitive impairment and worsening negative symptoms (Cuesta et al, 2014; Dean and Mittal, 2014; Mittal et al, 2014). In contrast to the current results, hyperkinetic movements (e.g., dyskinesias) appear to be more closely linked to aberrant dopaminergic processes and predict exacerbation of positive symptoms (Callaway et al, 2014; Mittal et al, 2010; Mittal et al, 2008; Mittal et al, 2007). …”
Section: Discussioncontrasting
confidence: 99%
“…It is important to note that our use of TICV allows this study to be compared with the existing literature because this method has been widely used in volumetric studies of UHR and schizophrenia patients (Hannan et al, 2010; Ho, Andreasen, Dawson, & Wassink, 2007; Ho, Andreasen, Ziebell, Pierson, & Magnotta, 2011; Mittal et al, 2010; Sullivan et al, 2000; Velakoulis et al, 2006; Ziermans et al, 2012). However, as alternative techniques become available, researchers in the UHR field will need to take steps to adopt them as well (e.g., a study designed to compare the TICV and TBV methods across brain structures in a large UHR sample).…”
Section: Discussionmentioning
confidence: 99%
“…Second, although our sample size is comparable to that used in many other high-impact UHR structural imaging investigations (Allen et al, 2011; Borgwardt, McGuire, et al, 2007; Borgwardt, Riecher-Rossler, et al, 2007; Broome et al, 2010; Fusar-Poli, Borgwardt, et al, 2011; Fusar-Poli, Broome, et al, 2011; Fusar-Poli, Stone, et al, 2011; Mittal et al, 2010; Morey et al, 2005; Niendam et al, 2006; Sabb et al, 2010; Stone et al, 2009), future studies with larger samples would be beneficial because increased power may allow for detection and control of potential confounding factors, which can threaten internal validity. A third, and related, limitation is the use of only one task to examine procedural learning.…”
Section: Discussionmentioning
confidence: 99%
“…During the adolescent prodromal period, when DA abnormalities escalate, 41 and potentially interact with extant early vulnerabilities (eg, signs of general motor system impairment pinpointed in archival and childhood home-video designs), 38 emerging specific motor signs such as hyperkinetic movements may serve as a highly sensitive prognostic indicator of basal ganglia dysfunction. 42 In support of this theory, prospective investigations in youth with prodromal syndromes have observed that the presence of specific motor abnormalities significantly increases the odds of developing psychosis in a brief 2-year period. 10,43 In a new exciting direction, some work also suggests that cerebellar-specific motor behavior (i.e., balance) may also have unique predictive value for negative symptoms as well.…”
Section: At Issuementioning
confidence: 96%